Role of Lithospheric Buoyancy Forces in Driving Deformation in East Africa From 3D Geodynamic Modeling - Tahiry A. Rajaonarison; D. Sarah Stamps; John Naliboff (Geophysical Research Letters)
Abstract Despite decades of investigation, the origin of forces driving continental rifting remains highly debated. Deciphering their relative contributions is challenging due to the nonlinear and depth‐dependent nature of lithospheric rheology. Recent geodynamic studies of the East African Rift (EAR) report contradicting results regarding the relative contribution of horizontal mantle tractions and lithospheric buoyancy forces. Here, we use high‐resolution 3D regional numerical modeling of the EAR to isolate the contribution lithospheric buoyancy forces to observed deformation. Modeled surface velocities closely match kinematic models of the Somalian Plate, Victoria Block, and Rovuma Block motions, but provide poor fit to along‐rift surface motions in deforming zones. These results suggest that lithospheric buoyancy forces primarily drive present‐day ∼E‐W extension across the EAR, but intrarift deformation may result from viscous coupling to horizontal asthenospheric flow.